Electrophysiological correlates of learning and cognitive control in children with tics with and without ADHD symptoms - Shephard, Elizabeth (2014)
The aims of this study were to explore the nature of comorbid Tourette syndrome and attention-deficit/hyperactivity disorder (TS+ADHD), in particular whether additive, independent or symptomatic phenocopy models of comorbidity can explain the co-occurrence of these two conditions, and to investigate the impact of comorbid ADHD symptoms on cognitive functions related to the control of tic symptoms in young people with TS. Electrophysiological activity and behavioural performance were measured during three cognitive tasks designed to assess goal-directed reinforcement learning, habit-based reinforcement learning, and cognitive control and were compared between young people with TS, ADHD, TS+ADHD and unaffected young people aged 9 to 17 years. The extent to which severity of tics, ADHD and comorbid oppositional-defiant disorder (ODD) symptoms predicted behavioural and electrophysiological correlates of reinforcement learning and cognitive control was also examined. The TS+ADHD and ADHD groups were impaired in goal-directed learning and modification of new behaviours using reinforcement feedback. ADHD symptoms were negatively associated with adaptive changes in the feedback-related negativity (FRN) ERP that were indicative of compensatory strategies employed to improve learning in the TS+ADHD group. In contrast, the TS+ADHD and ADHD groups showed intact habit-learning performance compared with unaffected controls. The TS+ADHD and ADHD groups were impaired in the ability to withhold inappropriate responses to Nogo stimuli during the Go/Nogo cognitive control task compared with TS and controls. Both ADHD groups also showed greater intra-individual variability than TS and controls. Concurrently, the TS+ADHD group were enhanced in the ability to withhold inappropriate Nogo responses and showed enhancement of the error-related negativity (ERN) ERP relative to the ADHD group. The TS group exhibited enhanced ERN ERPs and post-error slowing, a measure of the ability to adjust performance following errors. These findings are consistent with an additive, but interactive, model of comorbidity, and indicate that comorbid ADHD symptoms introduce impairments in young people with TS that will negatively impact upon the ability to control tics.